Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
ĐK : \(\orbr{\begin{cases}2-x\ge0\\x^2-4\ge0\end{cases}}\Leftrightarrow\hept{\begin{cases}x\le-2\\x=2\end{cases}}\)
\(\sqrt{2-x}-\sqrt{x^2-4}=0\)
\(\Leftrightarrow\sqrt{2-x}=\sqrt{x^2-4}\)
\(\Leftrightarrow2-x=x^2-4\)
\(\Leftrightarrow x^2+x-6=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=2\left(TM\right)\\x=-3\left(TM\right)\end{cases}}\)
Vậy \(S=\left\{2;-3\right\}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
đề phải là \(-3x-3\sqrt{x}>0\)
\(-3\left(x+\sqrt{x}\right)\)kết hợp đk của x
\(0< x< 1\)
\(< =>x+\sqrt{x}>0\)
\(< =>-3\left(x+\sqrt{x}\right)< 0\)
\(-3x-3\sqrt{x}< 0\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(6x\sqrt{2x^3+7}=6x^3+2x+22-4\sqrt{2x^3+7}\left(1\right)\) ĐK: \(\sqrt{2x^3+7}\ge0\)
Đặt \(\sqrt{2x^3+7}=a\ge0\)
\(\Rightarrow3a^2=6x^3+21\)
\(\Rightarrow\left(1\right)\Leftrightarrow6ax=3a^2+2x+1-4a\)
\(\Rightarrow\left(1\right)\Leftrightarrow3a^2+2x+1-4a-6ax=0\)
\(\Leftrightarrow\left(3a^2-4a+1\right)+2x\left(1-3a\right)=0\)
\(\Leftrightarrow\left(a-1\right)\left(3a-1\right)+2x\left(1-3a\right)=0\)
\(\Leftrightarrow\left(3a-1\right)\left(a-1-2x\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}a=\frac{1}{3}\\a=1+2x\end{cases}}\)
TH1: \(a=\frac{1}{3}\)
\(\Rightarrow\sqrt{2x^3+7}=\frac{1}{3}\)
\(\Leftrightarrow x^3=\frac{-31}{9}\)
\(\Leftrightarrow x=\sqrt[3]{\frac{-31}{9}}\left(tm\right)\)
TH2: a=1+2x
\(\Rightarrow\sqrt{2x^3+7}=1+2x\left(x\ge\frac{-1}{2}\right)\)
\(\Leftrightarrow2x^3+7=4x^2+4x+1\)
\(\Leftrightarrow x^3-2x^2-2x+3=0\)
\(\Leftrightarrow x^3-x^2-x^2+x-3x+3=0\)
\(\Leftrightarrow x^2\left(x-1\right)-x\left(x-1\right)-3\left(x-1\right)=0\)
\(\Leftrightarrow\left(x-1\right)\left(x^2-x-3\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=1\left(tm\right)\\x^2-x-3=0\left(2\right)\end{cases}}\)
Ta có: \(\Delta\left(2\right)=13\)
=> pt có 2 nghiệm pb \(\orbr{\begin{cases}x=\frac{1+\sqrt{13}}{2}\left(tm\right)\\x=\frac{1-\sqrt{13}}{2}\left(loai\right)\end{cases}}\)
Vậy ...
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\sqrt{\frac{2x-3}{x-1}}=2\)
\(\Rightarrow\frac{2x-3}{x-1}=2^2\)
\(\Rightarrow\frac{2.x-3}{x-1}=4\)
\(\Rightarrow2.x-3=4.\left(x-1\right)\)
\(\Rightarrow2.x-3=4.x-4\)
\(\Rightarrow2.x=4.x-1\)
\(\Rightarrow4.x-2.x=1\)
\(\Rightarrow2.x=1\)
\(\Rightarrow x=\frac{1}{2}\)